Constitutional and administrative law - Barnett, Hilaire (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Hilaire Barnett's Constitutional and Administrative Law has consistently provided students with reliable, accessible and comprehensive coverage of the Public Law syllabus. Mapped to the common course outline, the Fifteenth edition equips students with a thorough understanding of the UK constitution's past, present and future by analysing and illustrating the political and socio-historical contexts that have shaped the major rules and principles of constitutional and administrative law, as well as ongoing constitutional reform. This edition has been fully updated throughout, including a restructure to Chapters 22 and 26, as well as additional pause and reflect sections in order to aid student understanding of this complex area of the law. The online digital content also includes updates to the Multiple Choice Questions, Instructor Test Bank and Web Links. Ideal for students studying constitutional and administrative law for the first time, this is an indispensable guide to the challenging concepts and legal rules in public law"--
Introducing constitutional law -- Sources of the constitution -- The rule of law -- The separation of powers -- The royal prerogative -- Parliamentary sovereignty -- Structure and institutions of the European Union -- European Union law and national law -- Central government -- Ministerial responsibility -- Devolution and local government -- The electoral system -- Introduction to the House of Commons -- The legislative process -- Scrutiny of the executive -- The House of Lords -- Parliamentary privilege -- The protection of human rights -- Freedom of expression and privacy -- Freedom of association and assembly, public order and police powers -- State security -- Judges, the English legal system and tribunals -- Judicial review : introduction, jurisdiction and procedure -- Grounds for judicial review I : the substantive grounds for judicial review -- Grounds for judicial review II : procedural impropriety -- Ombudsmen and inquiries.
Includes bibliographical references and index.
Description based on print version record; resource not viewed.
Keywords: Constitutional law -- Great Britain; Administrative law -- Great Britain